Restaurant Management System (RMS) for Annapurna Restaurant and Cold Drinks - Maskar, Vidya; Bhosale, Samiksha; Kumbhar, Swapnaja; Karande, Taniskha; Chaudhari, Vaishnavi (International Journal of Computer Sciences and Engineering, 2024)
The Restaurant Management System (RMS) for Annapurna Restaurant and Cold Drinks is designed to streamline operations and enhance customer service through a dual-module approach. The Admin module allows restaurant owners to efficiently manage staff, oversee inventory, and monitor order statuses and billing in real-time. The Staff module enables employees to take and manage orders, track attendance, and update inventory if authorized, ensuring smooth day-to-day operations. This RMS not only reduces manual errors but also fosters better communication between staff and management, resulting in a more organized and customer-focused dining experience. In line with the final year project, the system incorporates data analytics, offering insights into sales trends, inventory usage, and customer preferences. These features empower the restaurant to make informed decisions, optimize stock levels, and adjust menu offerings based on data-driven analysis. Overall, the RMS reflects the growing importance of technology in improving efficiency and customer satisfaction.